Nutritional literacy status and its related factors in students of Yasuj University of Medical Sciences. - BAHRAMFARD, Tooba; OMID SALEHI, Sayed; AKBARTABAR TOORI, Mehdi; POURMAHMOUDI, Azizollah; JOWSHAN, Mohammadreza; PARVIN, Soraya; KHOSRAVANI, Zohreh; MALEKZADEH, Janmohamad (Nutrición Clínica y Dietética Hospitalaria, 2020)